Propagation of international supply-chain disruptions between firms in a country - Hiroyasu Inoue (Journal of Risk and Financial Management, 2021)
This study shows how import and export shocks propagate through domestic supply chains using actual Japanese supply-chain data and a world input-output table (WIOT) based on firm-level agent-based simulations. We propose three different models with which to connect the domestic firms to a WIOT. Then, we estimate the value-added losses of Japanese firms caused by shocks of different magnitudes and durations originating in China, in the EU and the US, and globally. The volume and rates at which losses increase are very different across the connection models, which indicates that the assignment of international connections to firms matters greatly. The losses increase sublinearly as the duration expands, which indicates that the shock propagation ultimately saturates the economy. Rates of saturation differ substantially depending on the assignment of international connections. The losses increase superlinearly as the initial reduction rate increases. This occurs because there is a greater probability of one supplier being replaced by other suppliers if the reduction is smaller.
Keywords: 330; propagation; simulation; supply chain; world input-output tables